Linguistic heritage of Stanislav Kazimirovich Rosovetsky - Dyadyshcheva-Rosovetska, Juliya; Rosovetsky, Stanislav (Current issues of Ukrainian linguistics: theory and practice, 2022)
he paper outlines a portrait of Stanislav Rosovetsky, a broad-based philologist who worked all his life in the field of Slavic studies, a scientist who operated an almost full range of philological tools and skillfully combined classical methods with the modern concepts. The research is focused on the linguistic heritage of an encyclopedically educated researcher, whose scientific interests included the development of professional methodology, aspects of studying the language of folklore, linguistics, historical lexicology, stylistics, history of Ukrainian literary language, terminological issues, methodological studies, mediaeval scholars. etc. The significance of his textbook "Ukrainian folklore in theoretical light", which became the culmination of many years of activity of the professor of Kyiv National Taras Shevchenko University, is considered from the linguistic point of view. There, the author describes the multifaceted links between folklore and linguistics; emphasis is placed on the impersonality of traditional folklore – because this aspect brings it closer to the language. The focus is also on folklorists’ understanding of new theories and research methods developed by linguists, which enriches the theory of the science of folklore. In addition, the application of methods of linguistic stylistics to the folklore language material is substantiated. The importance of borderline studies of folklore with dialectology is emphasized. Linguistic aspects of the fundamental work "Taras Shevchenko and Folklore" are outlined in the paper. The work of T. Shevchenko, not only a genius poet, linguist, founder of the new Ukrainian literary language, but also a bearer of traditional folklore occupied a special place in the scientific work of S. Rosovetsky. The emphasis on the linguistic and stylistic specifics of the embodiment of folklore methods of text organization in Shevchenko’s works – repetitions, psychological parallelisms, "Slavic negative parallelisms", "reservatio mentalis", etc. – is especially emphasized. The importance of differentiating Shevchenko’s folklore recordings made from memory and "voice" was also given a mention. The importance of the conclusions of the section «Language of the "Word... "», devoted to linguistic issues, and especially dialectological, in S. Rosovetsky’s monograph «"A Word about Igor’s Regiment" in Relations with Folklore» is observed.